Using the theories of fuzzy sets for researching the processes of diagnostics of data communication networks - Ibratbek Omonov (Diagnostyka, 2023)
This paper discusses the application of the queuing theory framework to analyze the diagnostic processes of data transmission networks (DTNs). It is shown that with the increasing complexity of DTN and existing tools and their diagnostic algorithms, it seems appropriate to create automated diagnostic systems taking into account the advantages and disadvantages of existing methods of network diagnostics. Available analytical and statistical (simulation modeling methods) are presented. From the point of view of the queuing system, closed, open (QS) analyzes are carried out and their characteristics are determined. An analysis of the statistical method of modeling the diagnostic system was carried out in the GPSS World environment. DTN diagnostic system models are considered in terms of closed and open queuing systems. The possibility of using QS for analytical models of DTN diagnostic systems is considered, as a result of which the general structure of the main elements and procedures for the operation of the diagnostic system are determined. By using the queuing theory, the speed and quality of data transmission is increased by diagnosing the elements of the data exchange process in the network.